Actual Problems and Prospects for the Development of Public-Private Partnership in Russia - Anatoly Yakovlevich Zaporozhan (Управленческое консультирование, 2018)
Russia is currently experiencing investment hunger, and the Russian economy is largely not to be invested. Public-private partnerships can serve as the main direction of the investment of the Russian economy. Only for this purpose it is necessary to radically restructure the state policy, improve legislation and to remove the imbalance of interests of public and private partners in the field of public-private partnership. Consideration of these issues and the future development of publicprivate partnership in RF in an article.